Answer to Question #212945 in Differential Equations for sasha

Question #212945
  1. solve each of the following

a) (6xy+2y2-5)dx +(3x2+4xy-6)dy=0 y(1)=2

b)x2d2y/dx2+xdy/dx+4y=2xlnx



1
Expert's answer
2021-07-05T16:54:07-0400

a) "(6xy+2y^2-5)dx +(3x^2+4xy-6) dy=0" , "y(1)=2"


"M(x,y)=6xy+2y^2-5 \\implies {\\partial M(x,y)\\over \\partial y}=M_y=6x+4y"


"N(x,y)=3x^2+4xy-6 \\implies {\\partial N(x,y)\\over \\partial x}=N_x=6x+4y"


Hence exact since "M_y=N_x"


There exist a function "\\mu(x,y)" such that

"{\\partial \\mu(x,y) \\over \\partial x}=M(x,y)=6xy+2y^2-5"


"{\\partial \\mu(x,y) \\over \\partial y}=N(x,y)=3x^2+4xy-6"


let "\\mu(x,y)=\\int^xM(x,y)dx" "+g(y)"


"=\\int^x(6xy+2y^2-5)dx" "+g(y)"


"=3x^2y+2xy^2-5x" "+g(y)"


"\\implies {\\partial \\mu (x,y) \\over \\partial y}=3x^2+4xy+{ \\partial g(y)\\over \\partial y}"


"\\implies 3x^2+4xy+{ \\partial g(y)\\over \\partial y}=3x^2+4xy-6"


"\\implies { \\partial g(y)\\over \\partial y}=-6"


"\\implies \\int dg(y)=-6 \\int dy"


"\\implies g(y)=-6y"


"\\implies \\mu(x,y)=3x^2y+2xy^2-5x-6y"


"\\therefore" The general solution is thus "3x^2y+2xy^2-5x-6y=c"

We can find the value of Cc using the initial condition "y(1)=2"

"\\implies3(1)^2(2)+2(1)(2)^2-5(1)-6(2)=c \\implies c=-3"

"\\therefore" the particular solution is

"3x^2y+2xy^2-5x-6y=-3"

Rearranging the equation gives

"3x^2y+2xy^2-5x+3=6y"

dividing through by 6 gives

"y={1\\over 2}x^2y+{1\\over 3}xy^2-{5\\over 6}x+{1\\over 2}"

b) "x^2{ d^2y\\over dx^2}+x{dy\\over dx}+4y=2xlnx"

This is a Cauchy's linear differential equation

let "x=e^z \\implies z=lnx"

let "x{dy\\over dx}=Dy" , "D={d\\over dz}"

let "x^2{ d^2y\\over dx^2}=D(D-1)y"

therefore the given equation becomes

"=D(D-1)y+Dy+4y=2ze^z"

"=(D^2-D+D+4)y=2ze^z"

"=(D^2+4)y=2ze^z"

Next we need to find C.F as follows

"D^2+4=0\\implies" "D=2i" and "D=-2i" where "i" is an imaginary number

"\\implies C.F=C_1e^{-2iz}+C_2e^{2iz}=C_1sin2z+C_2cos2z"

but "z=log" "x"

"\\therefore" "C.F=C_1sin 2logx+C_2cos2logx"

Next we need to find "P.I" as follows


"P.I={1\\over (D^2+4)}2ze^z=2e^z[{1\\over (D+1)^2+4}\\times z]=2e^z[{1\\over D^2+2D+5}]\\times z"

"={2e^z\\over 5}[{1\\over 1+{D^2+2D\\over 5}}]z"

"={2e^z\\over 5}[1+{D^2+2D\\over 5}]^{-1}z"

"={2e^z\\over 5}[1-{D^2+2D\\over 5}+...]z"

"={2e^z\\over 5}[z-{0^2+2\\over 5}]"

"={2e^z\\over 5}[z-{2\\over 5}]"

"={2ze^z\\over 5}-{4e^z\\over 25}"

but "x=e^z" and "z=lnx"

"\\implies P.I={2xlogx\\over 5}-{4logx\\over 25}"

"\\therefore" The general solution is given as


"y=CF+PI"

"y=C_1sin 2logx+C_2cos2logx+{2xlogx\\over 5}-{4logx\\over 25}"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog